A new species of aphid of the genus Nipponaphis (Hemiptera: Aphididae: Hormaphidinae) from China, inducing galls on the trunk of a witch-hazel (Hamamelidaceae) - Wang,Wei (2021)
ABSTRACT Plants and insects have co-existed for millions of years. Although research has been conducted on various insect species that induce galls on various plant tissues, information is particularly scarce when it comes to insects that form galls on the tough trunk of their host plants. This contribution describes the gall-inducing aphid Nipponaphis hubeiensis sp. nov. from the Zhushan County, Shiyan City, Hubei Province of China. This aphid induces enclosed galls with woody external layer on the trunk of Sycopsis sinensis (Saxifragales: Hamamelidaceae), an uncommon ecological niche in the aphid-plant interaction system. Morphological features for the identification of new species are provided. In addition, a partial sequence of the nuclear gene EF1α was amplified and sequenced to construct a cluster graph. Based on the clustering graph combined with morphology traits, the gall-forming aphid was classified into Nipponaphis. The unique ecological habits of this new aphid will bring innovative perspectives to the study of the evolution and diversity in aphid-host interaction.